Characterization of Bio‐oil from Hydrothermal Liquefaction of Organic Waste by NMR Spectroscopy and FTICR Mass Spectrometry1. Issue 1 (8th November 2012) - Leonardis, Irene; Chiaberge, Stefano; Fiorani, Tiziana; Spera, Silvia; Battistel, Ezio; Bosetti, Aldo; Cesti, Pietro; Reale, Samantha; De Angelis, Francesco
Abstract Solid wastes of organic origins are potential feedstocks for the production of liquid biofuels, which could be suitable alternatives to fossil fuels for the transport and heating sectors, as well as for industrial use. By hydrothermal liquefaction, the wet biomass is partially transformed into a water‐immiscible, oil‐like organic matter called bio‐oil. In this study, an integrated NMR spectroscopy/mass spectrometry approach has been developed for the characterization of the hydrothermal liquefaction of bio‐oil at the molecular level. 1H and 13C NMR spectroscopy were used for the identification of functional groups and gauging the aromatic carbon content in the mixture. GC–MS analysis revealed that the volatile fraction was rich in fatty acids, as well as in amides and esters. High‐resolution Fourier‐transform ion cyclotron resonance mass spectrometry (FTICR‐MS) has been applied in a systematic way to fully categorize the bio‐oil in terms of different classes of components, according to their molecular formulas. Most importantly, for the first time, by using this technique, and for the liquefaction bio‐oil characterization in particular, FT‐MS data have been used to develop a methodology for the determination of the aromatic versus aliphatic carbon and nitrogen content. It is well known that, because they resist hydrogenation and represent sources of polluting species, both aromatic molecules and nitrogen‐containing species raise concerns for subsequent upgrading of bio‐oil into a diesel‐like fuel.